Teachers'experiences on the teaching of listening and speaking skills in the senior phase English First Additional Language (EFAL) classrooms in Lepelle Circuit, Sekhukhune South District, South Africa: towards a communicative competence strategy - Nchabeleng, Bonolo Koruakae (My University, 2025)
In most multilingual societies, many learners face significant challenges in speaking English, as it is not their mother tongue (Sultana & Fang, 2024). English, taught as a First Additional Language (FAL) in South African schools, serves both as a medium of instruction and a critical tool for academic achievement. However, existing research highlights persistent obstacles such as limited vocabulary, language anxiety, and lack of fluency among learners, primarily due to minimal exposure to English outside the classroom and the dominance of indigenous languages in their daily communication (Alnefaie, 2024). Prior studies have often focused on these issues in urban or better-resourced settings, with limited attention paid to the unique challenges faced in rural, multilingual schools. This study builds on and extends the findings of previous research by examining the lived experiences of EFAL teachers in under-resourced, rural schools in the Lepelle Circuit, Sekhukhune South District, South Africa. Grounded in an interpretivist paradigm, the study employed a qualitative case study design to capture in-depth insights into how teachers navigate the socio-cultural and linguistic diversity of their classrooms while teaching listening and speaking skills. The participants included two EFAL teachers and 12 learners from Grades 8 and 9 in two purposively selected schools. Data collection involved semi-structured interviews, classroom observations, and analysis of learner performance with specific attention to fluency, accuracy, articulation, and communicative competence. The findings revealed that while prior research has documented general challenges such as language anxiety and lack of fluency, this study sheds light on how these challenges are amplified in rural multilingual settings by additional factors such as cultural norms, lack of parental support in English, and limited teaching materials. Teachers also faced difficulties in fostering learner participation, particularly in oral activities, due to learners’ fear of making mistakes and being ridiculed. However, the study also uncovered adaptive strategies teachers use, such as role-playing, group discussions, and targeted feedback to create more inclusive and supportive learning environments. By focusing on the rural, multilingual South African context, this study contributes new insights to the existing body of literature on English FAL instruction. It emphasizes the need for context-specific approaches and provides practical strategies for supporting the development of communicative competence in EFAL classrooms. The research calls for targeted teacher training, improved resource allocation, and the creation of learner-centered environments that encourage meaningful oral interaction. Ultimately, the study offers a valuable contribution toward addressing the persistent linguistic and educational inequalities in multilingual societies.
Thesis (Ph.D. (Language Education)) -- University of Limpopo, 2025
Keywords: Teaching; Learning; Assessment; Policy; Implementation; Listening; Speaking skills; Education; Active learning; English language; English language -- Study and teaching; Education, Secondary -- South Africa -- Limpopo; Listening -- Ability testing